2021
DOI: 10.1016/j.kint.2021.05.021
|View full text |Cite
|
Sign up to set email alerts
|

KDIGO 2021 Clinical Practice Guideline for the Management of Glomerular Diseases

Abstract: S28 Introduction S30 Summary of recommendation statements and practice points S88 Chapter 1: General principles for the management of glomerular disease S115 Chapter 2: Immunoglobulin A nephropathy (IgAN)/immunoglobulin A vasculitis (IgAV) S128 Chapter 3: Membranous nephropathy S140 Chapter 4: Nephrotic syndrome in children S153 Chapter 5: Minimal change disease (MCD) in adults S161 Chapter 6: Focal segmental glomerulosclerosis (FSGS) in adults S172 Chapter 7: Infection-related glomerulonephritis S187 Chapter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
883
0
32

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,214 publications
(1,121 citation statements)
references
References 916 publications
(1,541 reference statements)
8
883
0
32
Order By: Relevance
“…As a result, for an acceptable sample, at least 10 glomeruli are required 79 . This notion is supported by the recent guideline of the Kidney Disease: Improving Global Outcomes (KDIGO) organization on the management of glomerular diseases 80 . In case it is not yielded during the sampling, chances of missing the afflicted part of the kidney increase.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…As a result, for an acceptable sample, at least 10 glomeruli are required 79 . This notion is supported by the recent guideline of the Kidney Disease: Improving Global Outcomes (KDIGO) organization on the management of glomerular diseases 80 . In case it is not yielded during the sampling, chances of missing the afflicted part of the kidney increase.…”
Section: Discussionmentioning
confidence: 92%
“…This rate varies between 0.3 and 8.5% in the international reports 9 , 22 , 36 , 47 , 48 , 57 , 61 , 70 . A biopsy is still the “gold standard” for the diagnostic evaluation of glomerular diseases and the biopsy should be performed when the value of the information obtained from the biopsy exceeds the risk entailed 80 . Most of the renal biopsy indications (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has allowed providers in some situations to avoid the need to perform a kidney biopsy in patients who have with anti-PLA2R antibodies and rather to monitor them according to anti-PLA2R titers (204,205). This diagnostic strategy is now supported in the 2021 KDIGO Clinical Practice Guideline for the Management of Glomerular Diseases in not mandating a kidney biopsy to confirm PLA2R-associated MN in a seropositive patient (206). This is supported by our experience in which we see a lower frequency of PLA2R-positive kidney biopsies in our recent cohort, compared to historical studies suggesting that clinicians are already deciding not to biopsy patients diagnosed by the noninvasive serological test (33).…”
Section: Serologic Monitoring Of Diseasementioning
confidence: 99%
“…Over the past decade, growing clinical evidence has demonstrated that antimalarial drugs, mainly hydroxychloroquine (HCQ), show outstanding effectiveness and safety in the treatment of LN [ 4 ]. Several authoritative guidelines, such as KDIGO [ 5 , 6 ], and EULAR/ACR [ 7 ], recommend HCQ, in addition to corticosteroids and immunosuppressants, as a basic treatment for LN. Mechanistically, HCQ accumulates in lysosomes, elevating their pH values and resulting in impaired lysosomal proteolysis, which suppresses autoantigen presentation, inhibits endosomal Toll-like receptor signaling, and decreases proinflammatory cytokine production, to suppress immune cell-mediated inflammatory responses [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%